Pertumbuhan Plantlet Anggrek Phalaenopsis amabilis (L.) Blume pada Tahap Subkultur dengan Perlakuan Jenis Media dan Konsentrasi Pepton Berbeda - Anggi Krisdianto; Endang Saptiningsih; Yulita Nurchayati; Nintya Setiari (Prodi Magister Ilmu Biologi, Fakultas MIPA, Universitas Udayana, 2020)
Phalaenopsis amabilis is an orchid native of Indonesia that included in the appendix II category and one of the flowers included in the national and international flower trade, so that needs to be used in vitro propagation. The type of media used in the subculture determines the results of plantlet growth. Media used include New Phalaenopsis (NP), Vacint and Went (VW), and Murashige and Skoog (MS). Pepton as supplement added to the media. This study aims to analyze the different media types and peptone concentrations during the subculture. The method used is a plantlet subculture to a media bottle. This study uses a completely randomized design with 4x3 factorial patterns and 3 replications. Data were analyzed with ANOVA at 95% significance. Plantlet P. amabilis was subcultured in MS, VW and NP media with peptone (0; 1; 2; 3 g/L). Growth was observed for 2 months. The parameters observed were the number, length, width, appearance of leaves; number, length, appearance of the root. ANOVA test showed that the two treatments did not have interactions with all parameters, except leaf length. The results showed that the treatment of media type and peptone concentration significantly affected all parameters. NP media and peptone concentration of 3 g/L are the best media and concentrations for the number of leaves (5.67; 5.89), leaf appearance (19.83; 20.22 days ); leaf width (0.42; 0.47 cm), leaf length (1.47 cm); root length (2.83; 2.86 cm), number of roots (2.33; 2.56), and root appearance (28; 27.22 days). The combination of NP media with pepton concentration of 3 g/L is the best combination for the growth of P. amabilis plantlets at the subculture stage.